(untitled) (International Journal of Engineering and Computer Science, 2014)
The MANETs is to extend mobility into the realm of autonomous, mobile and wireless domains, where a set of nodes form the network routing infrastructure in an ad-hoc fashion. The majority of applications of MANETs are in areas where rapid deployment and dynamic reconfiguration are necessary and wired network is not available. In ad-hoc networks, nodes are not familiar with the topology of their networks. Instead, they have to discover it. The basic idea is that a new node may announce its presence and should listen for announcements broadcast by its neighbors. Each node learns about nodes nearby and how to reach them, and may announce that it, too, can reach them. The Multicast protocol can generally be categories into two: proactive and Reactive i.e On-Demand, DVMRP and PIM-DM . ODMRP is a mesh-based, rather than a conventional tree based, multicast scheme and uses a forwarding group concept. Three prominent multicast routing protocols are selected for performance protocols. The simulation environment Qualnet 5.0.2. The main aim is to calculate the relative feature and quality of each protocol.